ANALISIS KUALITAS LAYANAN TERHADAP TINGKAT KEPUASAN PENGGUNA INDRIVE DI KOTA PALEMBANG - Idpal, Idpal; Meiriza, Allsela; Oktadini, Nabila Rizky; Putra, Pacu; Sevtiyuni, Putri Eka (Universitas Methodist Indonesia, 2024)
User satisfaction will encourage them to use InDrive services, the results of the exploration with users reveal several problems such as server down and the application map display is not as intended to cause customer dissatisfaction with InDrive services. From this, it is hoped that this research will be a solution to the problem. To analyze the InDrive application, two kinds of methods are used, the ServQual and EUCS methods. The total number of respondents distributed was 100 people. The results of the analysis of the service quality level of the InDrive application in Palembang are Positive (+), with the results of the gap test between user perceptions and user expectations as a whole showing a value of 1.310, indicating that the InDrive application in Palembang has met user expectations. In the EUCS method, the results of the analysis of the Content Variable 4.08, Accuracy 4, Format 4.04, Ease of Use 3.96, and Timeliness 3.99 obtained the results of the analysis at the